The Influence of Financing Diversification and Financial Performance on the Risk of Islamic Commercial Banks in Indonesia - Raja Ria Yusnita (PT Mattawang Mediatama Solution, 2024)
This study aims to examine the influence of financing diversification, which includes six financing contracts of Islamic banks in Indonesia and financial performance on credit risk represented by NPF in Islamic commercial banks using regression panel data in 2018-2022. The results of this study indicate that there is an insignificant positive influence on financing diversification and financial performance partially on credit risk in Islamic banking in Indonesia. However, financing diversification and financial performance together have a significant influence on credit risk, which is currently a concern of the Islamic bank financial services authority in Indonesia. The financial performance measurement indicators in this study only focus on ROA, and this indicator may have limitations in measuring the financial performance of Islamic banking.